2017
DOI: 10.1111/dar.12521
|View full text |Cite
|
Sign up to set email alerts
|

Controlling behaviours and technology‐facilitated abuse perpetrated by men receiving substance use treatment in England and Brazil: Prevalence and risk factors

Abstract: Introduction and AimsControlling behaviours are highly prevalent forms of non‐physical intimate partner violence (IPV). The prevalence of perpetrating controlling behaviours and technology‐facilitated abuse (TFA) was compared by men receiving substance use treatment in England (n = 223) and Brazil (n = 280). Factors associated with perpetrating these behaviours towards their current/most recent partner and their association with other types of IPV were explored.Design and MethodsSecondary analysis from two cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
(72 reference statements)
2
10
0
Order By: Relevance
“… illustrate the importance of expectancies about the effects of alcohol in relation to IPV perpetration, consistent with previous work showing strong cultural expectancies that alcohol facilitates IPV . There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma . However, Madruga et al .…”
supporting
confidence: 81%
See 2 more Smart Citations
“… illustrate the importance of expectancies about the effects of alcohol in relation to IPV perpetration, consistent with previous work showing strong cultural expectancies that alcohol facilitates IPV . There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma . However, Madruga et al .…”
supporting
confidence: 81%
“…Gilchrist et al [18] illustrate the importance of expectancies about the effects of alcohol in relation to IPV perpetration, consistent with previous work showing strong cultural expectancies that alcohol facilitates IPV [19]. There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma [20,21]. However, Madruga et al [22] found that although witnessing parental violence was independently associated with being a victim of IPV, IPV perpetration was not associated with witnessing parental violence when experience of direct violence as a child was controlled for.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…A recent meta-analysis of the effectiveness of perpetrator interventions to reduce IPA by men who use substances (five of the nine trials were conducted in community ( n = 4) or inpatient ( n = 1) substance use treatment settings) concluded that integrated interventions targeting both IPA and substance use were not superior in reducing IPA than substance use treatment alone [ 23 ]. Physical IPA was the main outcome reported in the majority of trials, despite the perpetration of emotional abuse, coercive control and technology-facilitated abuse also being highly prevalent in this group [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of intimate partner violence (IPV) perpetration by men in substance use treatment are high (Gilchrist et al , 2015; Gilchrist, Canfield, Radcliffe and d’Oliveira, 2017; Kraanen et al , 2014; Taft et al , 2010). IPV refers to any kind of violence against partners in intimate relationships including physical (hitting, kicking, shoving, etc.…”
Section: Introductionmentioning
confidence: 99%